Train Your Brain for Success : Read Smarter, Remember More, and Break Your Own Records - Seip, Roger, 1970- (Gildan, 2019)
Train Your Brain for Success explains specific ways of thinking and acting that will get anyone where they want to go, fast. Learn to condition your mind to move toward success automatically, by discovering greater memory power and fundamental techniques for boosting reading speed and comprehension.